Jupiter's legacy. Volume 4 - Millar, Mark; Millar, Mark; Quitely, Frank, 1968- (Image Comics, Inc., 2020)
"The superheroes have taken over the world, and only the supervillains can save us from their disastrous mistakes and monumental hubris. Hutch and Chloe have been in hiding with their son, but now they're gathering a team of supervillains to go back to America to retake the White House in the name of all humanity. This is a must-read modern classic!"--Publisher's website.